2023
DOI: 10.31083/j.jin2202034
|View full text |Cite
|
Sign up to set email alerts
|

Digital Therapeutics for Insomnia: Assessing the Effectiveness of a Computerized Home-Based Cognitive Stimulation Program

Abstract: Background: Sleep disturbances represent a major health burden today, affecting up to one-third of the population worldwide. Computerized cognitive stimulation has been proven as an effective approach in diminishing negative symptomatology and improving the quality of life in a range of medical conditions. Given its nature in enhancing neural networks, such as those involved in stimulus monitoring and inhibitory processes, computerized cognitive stimulation is arising as a potential tool to overcome underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Regarding quality of life, the benefits of cognitive stimulation interventions remain uncertain. While some studies have shown improvements in quality of life in individuals with clinical insomnia after just seven sessions [ 74 ], studies in healthy elderly populations have not found significant differences in quality of life after either short-term (24 sessions performed twice a week) [ 117 ] or long-term (over 12 months) [ 118 ] cognitive stimulation programs that use electronic devices. Despite finding contradictory results in the literature, those studies that have included more than one training session per week, as in our case, have consistently reported improvements [ 109 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding quality of life, the benefits of cognitive stimulation interventions remain uncertain. While some studies have shown improvements in quality of life in individuals with clinical insomnia after just seven sessions [ 74 ], studies in healthy elderly populations have not found significant differences in quality of life after either short-term (24 sessions performed twice a week) [ 117 ] or long-term (over 12 months) [ 118 ] cognitive stimulation programs that use electronic devices. Despite finding contradictory results in the literature, those studies that have included more than one training session per week, as in our case, have consistently reported improvements [ 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…Advances in the understanding of this neural functioning have led to the development of a range of therapeutic applications in the form of cognitive stimulation interventions, which aim to improve brain function by increasing the strength and efficiency of neural connections [ 69 , 70 , 71 , 72 ]. These interventions can take the form of computer-based training programs or cognitive rehabilitation, and have been shown to be effective in improving cognitive function in individuals with a range of neurological and psychiatric disorders [ 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. Therefore, considering the promising results from other diseases that are also linked to cognitive dysfunction, non-pharmacological intervention approaches based on cognitive stimulation represent a potential solution [ 80 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…CogniFit’s general cognitive assessment (CAB) is an online neurocognitive assessment that aims to evaluate cognitive functions in the following domains: attention, perception, memory, executive functions, coordination, and physical, psychological, and social wellbeing. This instrument has been widely used for cognitive assessment ( Yaneva and Mateva, 2017 ; Sánchez-Sansegundo et al, 2021 ; Berbegal et al, 2022 ; Tapia et al, 2022 , 2023a , 2023b ; Duñabeitia et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%